The Perception of MSME in Tegal City on Readiness Towards MSME’S Digitalization in The New Normal Era - Ida Farida; Aryanto Aryanto (Jurnal Riset Akuntansi Terpadu, 2021)
The Covid-19 pandemic caused a crisis in all fields, this pandemic had a wide impact on the business world at all levels, MSMEs were the hardest hit. Data from the Ministry of Cooperatives and MSMEs, totaling 163,713 MSMEs, were affected by the Covid-19 pandemic. The Ministry of Cooperatives and SMEs has set a digitization target of 10 million MSMEs by 2020. The existence of this digitalization opportunity has not been optimally utilized by MSME players. Of the approximately 64 million MSME population in Indonesia, only 13% are connected to the digital ecosystem (Kominfo.co.id, 2020). There are 930 UMKM players in Tegal City from a total of 1940 UMKM recorded by the Cooperative Office. Of the number of MSMEs, some were able to survive and some had to close their businesses in the end. This is because some MSME players have not digitized their business. Perceptions of usefulness, perceived ease of use, and HR competence are factors that also influence MSME actors to readiness in implementing digitalization of their business. The purpose of this study was to determine the effect of perceived usefulness, perceived ease of use, and HR competence on the readiness of MSMEs towards business digitization in the new normal era. The results of this study indicate that the perceived usefulness variable has no effect on the readiness of MSMEs towards digitalization, while the variables of perceived ease of use and HR competencies have an effect on the readiness of MSMEs towards digitization.